2020
DOI: 10.1563/aaid-joi-d-19-00228
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Torque Values of Abutment Screws After Dynamic Loading: Effects of Sealant Agents and the Taper of Conical Connections

Abstract: This in vitro study evaluated the influence of taper angles on the internal conical connections of implant systems and of the application of chlorhexidine gel as an antibacterial agent or a polyvinyl siloxane (PVS) sealant on the reverse torque values of abutment screws after dynamic loading. The current study tested four implant systems with different taper angles (5.4°, 12°, 45°, and 60°). Specimens were divided into three groups: control (neither chlorhexidine gel filled nor silicone sealed), 2% chlorhexidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Other authors have reported results consistent with ours [ 20 , 26 ]. On the other hand, Ozdiler et al [ 27 ] reported a higher percentage loss of RTV in the sealing silicone gel group than in the other groups, with a significant difference. Notably, the authors only registered the RTV after cyclic loading.…”
Section: Discussionmentioning
confidence: 97%
“…Other authors have reported results consistent with ours [ 20 , 26 ]. On the other hand, Ozdiler et al [ 27 ] reported a higher percentage loss of RTV in the sealing silicone gel group than in the other groups, with a significant difference. Notably, the authors only registered the RTV after cyclic loading.…”
Section: Discussionmentioning
confidence: 97%
“…Different methodology and variations in the form of contamination (for saliva; natural vs. artificial and for chlorhexidine; gel vs. liquid; wettability) and concentration may also account for differences in results between studies. In addition, the lack of simulating oral condition seems to be an effective factor for variation in reported results [18,26,27]. Despite the relatively high risk of blood and fluoride contamination of the abutment screw in clinical practice, a few studies on blood and fluoride contamination of the abutment screw have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Different methodology and variations in the form of contamination (for saliva; natural vs. artificial and for chlorhexidine; gel vs. liquid; wettability) and concentration may also account for differences in results between studies. In addition, the lack of simulating oral condition seems to be an effective factor for variation in reported results [ 18 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%